New verifiable outsourced computation scheme for an arbitrary function. (2016) - Xiang, Can; Tang, Chunming
We study the construction of efficient verifiable outsourced computation for arbitrary functions. We improve previous verifiable outsourced computation schemes for arbitrary functions by using hybrid encryption based on fully homomorphic encryption and introducing multi-free gates in circuits, which can efficiently outsource the computation of an arbitrary function f on arbitrary input x to an untrusted cloud server, and reduce the one-time security error and the client's computation cost. Moreover, our scheme can greatly reduce online communication cost. Finally, we prove the security and the efficiency of our scheme.